In vitro bactericidal activity of blue light (465 nm) phototherapy on meticillin‐susceptible and meticillin‐resistant Staphylococcus pseudintermedius. Issue 5 (22nd May 2017) - Schnedeker, Amy H.; Cole, Lynette K.; Lorch, Gwendolen; Diaz, Sandra F.; Bonagura, John; Daniels, Joshua B.
Abstract : Background: Staphylococcus pseudintermedius is the most common cause of bacterial skin infections in dogs. Meticillin‐resistant infections have become more common and are challenging to treat. Blue light phototherapy may be an option for treating these infections. Hypothesis/Objectives: The objective of this study was to measure the in vitro bactericidal activity of 465 nm blue light on meticillin‐susceptible Staphylococcus pseudintermedius (MSSP) and meticillin‐resistant Staphylococcus pseudintermedius (MRSP). We hypothesized that irradiation with blue light would kill MSSP and MRSP in a dose‐dependent fashion in vitro as previously reported for meticillin‐resistant Staphylococcus aureus (MRSA). Methods: In six replicate experiments, each strain [MSSP, n = 1; MRSP ST‐71 (KM1381) n = 1; and MRSA (BAA‐1680) n = 1] were cultivated on semisolid media, irradiated using a 465 nm blue light phototherapeutic device at the cumulative doses of 56.25, 112.5 and 225 J/cm 2 and incubated overnight at 35°C. Controls were not irradiated. Colony counts (CC) were performed manually. Descriptive statistics were performed and treatment effects assessed using the Wilcoxon–Mann – Whitney rank‐sum test. Bonferroni‐corrected rank‐sum tests were performed for post hoc analysis when significant differences were identified. Results: There was a significant decrease in CC with blue light irradiation at all doses for MRSA ( P = 0.0006) but not for MSSP ( P = 0.131) or MRSP ( P = 0.589). Conclusions: Blue light phototherapy significantly reduced CC of MRSA, but not of MSSP or MRSP. The mechanism for the relative photosensitivity of the MRSA isolate is unknown, but is hypothesized to be due to an increased concentration of porphyrin in S. aureus relative to S. pseudintermedius, which would modulate blue light absorption. Abstract : Background – Staphylococcus pseudintermedius is the most common cause of bacterial skin infections in dogs. Meticillin‐resistant infections have become more common and are challenging to treat. Blue light phototherapy may be an option for treating these infections.Hypothesis/Objectives – The objective of this study was to measure the in vitro bactericidal activity of 465 nm blue light on meticillin‐susceptible S. pseudintermedius (MSSP) and meticillin‐resistant S. pseudintermedius (MRSP). We hypothesized that irradiation with blue light would kill MSSP and MRSP in a dose‐dependent fashion in vitro as reported previously for meticillin‐resistant Staphylococcus aureus (MRSA).Conclusions – Blue light phototherapy significantly reduced CC of MRSA, but not of MSSP or MRSP. The mechanism for the relative photosensitivity of the MRSA isolate is unknown, but is hypothesized to be due to an increased concentration of porphyrin in S. aureus relative to S. pseudintermedius, which would modulate blue light absorption.